Hydrophobin-like proteins in aerial conidia of three entomopathogenic hyphmycetes as fungal biocontrol agents: contents and SDS-PAGE profiles - YING Sheng-hua; DENG Mi-xia; FENG Ming-guang (浙江大学学报. 农业与生命科学版)
Contents of hydrophobin-like proteins (HLP) extracted from aerial conidia of 14 isolates of Beauveria bassiana, Paecilomyces fumosoroseus and Metarhizium anisopliae varied significantly among the three fungal species and their isolates. Of those, the maximal HLP content in B. bassiana 2861 conidia was up to 23.4 μg·mg-1, 3.7 times greater than the minimal level of M. anisopliae 297 (5.0 μg·mg-1). Based on SDS-PAGE analysis, the HLP components differed among the three fungal species with the major molecules of 12.0, 15.0 and 17.5 kDa in 6 B. bassiana isolates and of 15.0 and 17.5 kDa in 5 P. fumosoroseus isolates. However, the HLP components were more variable within M. anisopliae with the molecules of 17.0 and 14.5 kDa in the isolate Ma2125, 19.0 and 13.5 kDa in Ma0201, and only 13.5 kDa in Ma297. Moreover, the aerial conidia, aerial mycelia and submerged mycelia of B. bassiana 2860 isolate grown on Sabouraud dextrose medium with or without agar differed significantly in their HLP contents (26.3, 18.2 and 16.5 μg·mg-1 respectively), which consistently consisted of the molecules of 15.0 and 17.5 kDa. The inter- and intraspecific variations in HLP contents and components are discussed in association with the understanding of their possible role in ecological adaptation and formulation enhancement.